Đề nghị một phương pháp xây dựng phần mềm dạy học - Thành, Đỗ Văn; Tuyết, Ngô Ánh (Journal of Computer Science and Cybernetics, 2016)
Constructing Tutoring System on Computer Network is a problem that is being interested by researchers. The main of  this paper is to introduce a method for constructing a Tutoring System via presenting one for concrete problem of geometry. The Tutoring System describes approximately process of studying and teaching in class. The paper proposes a method for presenting pupil actions in a defined studying session. This presentation method permits to diagnostic knowledge status of pupils and to help them in any time in the studying session. The  experiment Tutoring System confirms possibitity of distance  education automatically controlled by computers.